2021
DOI: 10.3389/fsurg.2021.609719
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Tumor Abnormal Protein Preoperatively Predicts Poor Prognosis of Patients With Esophageal Squamous Cell Carcinoma

Abstract: Background: Esophageal squamous cell carcinoma (ESCC) acts as a fatal malignant tumor among human beings and is marked by late-stage diagnosis, frequent recurrence, metastasis, and therapy resistance. Tumor abnormal protein (TAP) remarkably affects cancer development and progression of human cancers. TAP has been shown to be a biomarker for gastric and lung cancer progression. Nevertheless, the clinical value exhibited by TAP for ESCC has not been well-explained in the current literature.Methods: The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…This indicates that the increased TAP is related to the poor prognosis of GC patients after surgery, which is consistent with previously reported. 21 …”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the increased TAP is related to the poor prognosis of GC patients after surgery, which is consistent with previously reported. 21 …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies suggested that there was a close relationship between TAP and the prognosis of patients with various cancers. For example, Wu et al [12]indicated that TAP could be regarded as a prognostic factor for NSCLC patients, and Yao et al [13] revealed that high preoperative TAP level could predict the poor outcome of patients with esophageal squamous cell carcinoma. In line with these ndings, this study suggested that there was a positive correlation between higher preoperative TAP and prognosis of HCC after curative resection, and multivariate analysis con rmed that it was a signi cant prognostic factor of RFS.…”
Section: Discussionmentioning
confidence: 99%
“…When TAP presents in blood, it will react with detection reagent (Abnormal Sugar Chain Structure of Glycoproteins) and generates a crystal-like condensation product. According to previous studies [13], TAPpositive was de ned as condensation particle area ≥ 225 µm 2 , TAP weakly positive was de ned as the condensation particle area was between 121 and 225 µm 2 , and as for TAP-negative, there was no crystallike condensation product. In the present study, high expression group has a condensation particle area that was ≥ 225 µm 2 , and low expression group has a condensation particle area that was < 225 µm 2 .…”
Section: Data Collection and Tap Detectionmentioning
confidence: 99%
See 2 more Smart Citations